PREVALENSI PENYAKIT KULIT AKIBAT INFEKSI PARASIT YANG SERING TERJADI DI PESANTREN D H MEDAN 2018 - FANNY KHAIRIAH SIREGAR; HEPPY JELITA SARI BATUBARA (JURNAL ILMIAH MAKSITEK, 2021)
Scabies and pediculosis capitis are diseases related to personal hygiene and environmental sanitation. Low levels ofcleanliness, difficult acces to water, and occupancy density can increase the prevalence of scabies and pediculus capitis.The purpose of this study was to determine the prevalence of scabies and pediculus capitis that occurres in the DarulHikmah Islamic boarding school in Medan. This type of research is observational descriptive with cross sectional designwhere the variables are measured in one measurement without intervening. The population in this study were boardingschool students or santri who lived in the Darul Hikmah Islamic Boarding School in Medan. The sample size was 250 people.The result of this study shows that the prevalence of scabies is 85,2% and prevalence of pediculus capitis is 90%.Environmental sanitation in the Darul Hikmah Islamic Boarding School in Medan is the good category (57,25). However,personal hygiene is still in moderate category (90,4%). That the prevalence of pediculosis capitis is higher than theprevalence of scabies. Suggestions from the result of this study are that health workers are expected to eradicate scabiesand pediculosis capitis in the Darul Hikmah Islamic Boarding School in Medan by conducting mass treatmen and healtheducation.